Implication of Innovation, Green and Digital Economy for MSME: Viera Oleh-Oleh Pekanbaru As A Case Study - Rasyid, Muhammad; Syafi’I, Ahmad; Silviano, Haykal; Prasetia, Aditia; Nofirda, Fitri (Jurnal Ilmiah Manajemen Kesatuan, 2023)
This research discusses the positive impact of innovation and the development of green and digital economies on the Viera Oleh-Oleh MSMEs. These MSMEs have successfully utilized digital currency, social media, and e-commerce to enhance transaction efficiency and product promotion. The implementation of digital technology, such as computer-based cash registers, has also contributed to improving operational productivity. Furthermore, Viera Oleh-Oleh MSMEs have enhanced product quality and environmental awareness by using sustainable local materials and reducing plastic usage. The use of digital technology and green economic principles helps Viera Oleh-Oleh MSMEs survive and thrive in the current digital and economic era. These innovations not only provide a competitive advantage but also meet the demands of consumers increasingly concerned about sustainability. Through the implementation of these strategies, Viera Oleh-Oleh MSMEs can leverage business growth and support to achieve better performance.